Pengaruh Penerapan Model Pembelajaran Mind Mapping terhadap Kemampuan Berpikir Kreatif Matematis Siswa Kelas IV Sekolah Dasar - Istari, Putri; Bistari, Bistari; Pranata, Rio (AS-SABIQUN, 2023)
The goal of this study is to describe the effect of application the mind mapping learning model on the mathematical creative thinking skills of fourth grade students at elementary school using a Nonequivalent control group in experimental research. 34 students from class IV A (the experimental class) and 35 students from class IV C (the control class) from SD Muhammadiyah 2 Pontianak made up the research sample. Data collection methods using instruments like essay tests and measurement methods. According to the findings of a statistical analysis. The experimental class's pre-test and post-test results were 36 and 67, respectively. Pre test and post test results for the control group scores were 40 and 55, respectively. Based on the results of the t-test calculation, tcount (4.202)> ttable (1.996) (α = 5% and dk = 67), Ha is then approved. Results are up to 0.7 in the medium criteria according to the effect size calculation. Thus, it can be said that the use of the mind mapping learning paradigm has a beneficial effect on class IV elementary school students' capacity for creative mathematical thought.